Pedestrian Injury Patterns and Risk in Minibus Collisions in China - Li, Kui (Med Sci Monit, 2015)
BACKGROUND: The minibus, with a nearly flat front, is widely used in China, especially in the underdeveloped regions, and results in large numbers of pedestrian injuries and deaths. The purpose of this study was to determine the injury patterns and risk for pedestrians involved in these crashes. MATERIAL/METHODS: We conducted an in-depth investigation of minibus/pedestrian accidents in Chongqing, China, occurring between September 2000 and April 2014. The enrolled pedestrians was classified into 3 groups: young (aged 14–44 years), middle-aged (aged 45–59 years), and elderly (aged over 60 years). Pedestrian injuries were coded according to the Abbreviated Injury Scale (AIS). RESULTS: A total of 109 pedestrians, with an average age of 55.7±16.2 years, were injured or killed – 30.3% were young, 23.9% were middle-aged, and 45.9% were elderly. Pedestrians hit by a minibus had a high proportion of head, chest, and extremity injuries – 84.4%, 50.5%, and 52.3%, respectively. In addition, impact speeds in excess of 75 km/h all ultimately resulted in fatalities. At an impact speed of 30 km/h, the risk of pedestrian fatality and AIS3+ injury are approximately 12.0% and 37.2%, respectively. At 50 km/h the risks are 65.2% and 96.9%, respectively, and at 70 km/h the risks are 96.3% and 99.9%, respectively. CONCLUSIONS: A higher likelihood of chest injury was associated with being older and impact speed of over 40 km/h in minibus/pedestrian collision. Our data suggest that the injury patterns of pedestrians in minibus collisions differ from that in other vehicle/pedestrian collisions. These findings could contribute to better understanding of the injury patterns and risk of pedestrian in minibus collisions in China, which may play an important role in developing measures to improve traffic safety.